PELATIHAN PEMBUATAN NPWP BAGI MAHASISWA PRODI AKUNTANSI SEMESTER 5 POLITEKNIK PAJAJARAN ICB BANDUNG DENGAN METODE PRAKTIK MENGGUNAKAN WEB PAJAK CORETAX - Gunardi; Priatna Kesumah (ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
Community service is one form of implementing the Tri Dharma of Higher Education. This activity aims to improve students’ understanding and skills in creating a Taxpayer Identification Number (NPWP) online through the Coretax tax platform. The target participants were 25 fifth-semester students of the Accounting Study Program at Politeknik Pajajaran ICB Bandung. The method used was direct practice in online NPWP registration. The results showed that all participants were able to understand the procedures and successfully create their NPWP. Through this activity, students are expected to be better prepared to fulfill their tax obligations as taxpayers while also gaining additional competence in tax administration.